Activated carbon nanofiber produced from electrospun PAN nanofiber as a solid phase extraction sorbent for the preconcentration of organophosphorus pesticides. Issue 4 (4th March 2017) - Maddah, Bozorgmehr; Soltaninezhad, Mostafa; Adib, Korosh; Hasanzadeh, Mahdi
ABSTRACT: Activated carbon nanofibers (CNFs) were derived from electrospun nanofibers with subsequent heat treatment. They were characterized by scanning electron microscopy and Fourier transform infrared spectroscopy. The applicability of activated CNFs for preconcentration and determination of organophosphorus pesticides (OPPs) was investigated by high-performance liquid chromatography with diode array detector (HPLC-DAD). Some important parameters influencing the extraction efficiency, such as amount of sorbent, pH, flow rate and amount of salt, were investigated by response surface method (RSM). The obtained results showed that this analytical method will be useful for the analysis of OPPs in tap water with high precision and accuracy.